Study on the Curative Effect and Safety of Radiofrequency Catheter Ablation of Paroxysmal Atrial Fibrillation via Zero-Fluoroscopy Transseptal Puncture under the Dual Guidance of Electroanatomical Mapping and Intracardiac Echocardiography. (24th May 2021) - Hang, Fei; Cheng, Liting; Liang, Zhuo; Dong, Ruiqing; Wang, Xinlu; Wang, Ziyu; Wang, Zefeng; Wu, Yongquan
Abstract : Aims . 3D electroanatomical mapping combined with intracardiac echocardiography- (EAM-ICE-) guided transseptal puncture has been proven safe and effective during the radiofrequency catheter ablation (RFCA) procedure used to treat paroxysmal atrial fibrillation (PAF). In this study, we aimed to compare the curative effect and safety of RFCA via F (fluoroscopy) and zero-fluoroscopy transseptal puncture guided by EAM-ICE in patients with PAF. Methods and Results . A prospective study in which 110 patients with PAF were included and assigned to two groups was conducted. Fifty-five (50%) patients were enrolled in the EAM-ICE group, whereas the other 55 (50%) patients were enrolled in the F group. There were no significant differences in baseline characteristics between the two groups. The transseptal duration time was longer in the EAM-ICE group (19.8 ± 3.0 min vs. 8.6 ± 1.2 min, p ≤ 0.01 ); however, fluoroscopy was not used in the EAM-ICE group compared with the F group (0 mGy vs. 109.1 ± 57.9 mGy). Similarly, there was also no significant difference in the recurrence rate of atrial fibrillation between the EAM-ICE and F groups (25.5% vs. 18.2%, p = 0.356 ). Conclusion . RFCA via EAM-ICE-guided zero-fluoroscopy transseptal puncture in patients with PAF is safe and effective for long-term follow-up.